Роль скрининговой ультразвуковой диагностики в оценке состояния эндометрия - Сюсюка, В. Г.; Островский, А. И.; Разыграева, М. А.; Susuka, V. G.; Ostrovski, А. I.; Razigraeva, М. А.; Сюсюка, Володимир Григорович (МЕДИ Экспо, 2016)
Based on a comprehensive survey of 25 women with abnormal endometrial findings set discrepancy ultrasound diagnosis and further histopathological examination in 40% of patients. However, the difficulty in the differentiation of diffuse and focal hyperplasia of the endometrium is the most frequent erroneous conclusion, does not affect the further tactics to verify the diagnosis. At the same time we should not forget that the conclusion of an ultrasonic diagnosis depends on many technical factors, including subjective.
Role of screening ultrasound diagnostics in the assessment of endometrial
Keywords: тези